The effects of water markets: Evidence from the Rio Grande. (November 2020) - Debaere, Peter; Li, Tianshu
Highlights: Water markets shift crop compositions towards high-value crops. Water's economic productivity increases esp. with droughts. Differences-in-differences methods are necessary to properly assess their effect. Abstract: We present empirical evidence of the impact of water markets on agricultural production. From 1954 to 2012, we compare the crop composition in counties of the Rio Grande water market with neighboring control counties before and after the establishment of the water market in 1971. What we find is consistent with water markets facilitating a shift from low- to high-value crops, or, in terms of our empirical proxies, from less productive crops that generate on average less dollars per unit of water to ones that are more productive. We find that such reallocations are especially prevalent in times of drought.